African genetics for human society. (November 2018) - Unknown
We are inviting presubmission enquiries for Articles, Perspectives and Analyses on human, animal, plant and microbial genetics and genomics from Africa, by corresponding authors living and working in African countries, with the aim of publishing an issue of the journal devoted to African genetics.